Analisis upaya Pelestarian Arisp Statis di Dinas Perpustakaan dan Kearsipan Provinsi Lampung - M. Zakky Al Hafizd; Reza Nawafella Alya Parangu; Rahmat Iqbal (Program Studi Perpustakaan dan Sains Informasi UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study analyzes efforts to preserve static archives at the Lampung Provincial Library and Archives Service using the standard reference of the guidelines of the Regulation of the Head of the National Archives of the Republic of Indonesia Number 23 of 2011 concerning Guidelines for Static Archive Management. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The informant in this study is a static archive archivist. The results of the study show that preventive and curative preservation has been carried out according to standards, with the support of digitalization cooperation with ANRI. However, there are obstacles in the form of the use of materials that are not yet lignin-free, the absence of independent restoration spaces, as well as limited human resources, and budgets that hinder preservation programs. It is necessary to improve human resource competence, eliminate standards for preservation materials, and strengthen the budget so that the static archives of Lampung Province can be maintained as the collective memory of the nation.